ChemInform Abstract: Low‐Temperature Synthesis of Cu2CoSnS4 Nanoparticles by Thermal Decomposition of Metal Precursors and the Study of Its Structural, Optical and Electrical Properties for Photovoltaic Applications. Issue 5 (January 2016) - Krishnaiah, Mokurala; Bhargava, Parag; Mallick, Sudhanshu
Abstract: Cu2 CoSnS4 (CCTS) nanoparticles are prepared from a 1.85:1:1:12 molar mixture of Cu(OAc)2, CoCl2, SnCl2, and CS(NH)2 in EtOH which is ball milled prior to thermal decomposition (alumina crucible, 250‐450 °C, 1‐6 h).